Development of automated plagiarism detection system - Tan, Jun Long (Nanyang Technological University, 2022)
This final year project “Development of Automated Plagiarism Detection System” aims to develop a standalone web-based system for detecting and calculating the similarity between students’ codes based on C Programming Language.